Establishing junior colleges, a report of a national conference sponsored by ucla, the aajc, and the commission for accrediting junior colleges of the western association of schools and colleges (los Angeles, July 10-12, 1963) - California Univ., Los Angeles; California Univ., Los Angeles ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1964)
Principles and practices in the establishment of new colleges were discussed in a series of 18 papers. Specific topics included time-sequence factors, establishment of student personnel services, providing plant and facilities, securing and organizing personnel, developing community relations, curriculum development, and financing. This document is also available for $1.50 from ucla students' store, 405 hilgard avenue, los Angeles, California 90024. (wo)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Planning; College Role; Community Relations; Conference Reports; Curriculum Development; Development; Educational Facilities; Faculty Recruitment; Program Development; Public Relations; School Community Relationship; School Expansion; School Location; Student Personnel Services; Teacher Education; Two Year Colleges